Coupled analysis of vehicle stability in crosswind on low adhesion road. Issue 8 (12th September 2018) - Li, Shuya; Gu, Zhengqi; Huang, Taiming; Chen, Zhen; Liu, Jun
Abstract : Purpose: The purpose of this paper is to develop a two-way coupling approach for investigating the aerodynamic stability of vehicles under the combined effect of crosswind and road adhesion. Design/methodology/approach: The author develops a new two-way coupling approach, which couples large eddy simulation with multi-body dynamics (MBD), to investigate the crosswind stability on three different adhesion roads: ideal road, dry road and wet road. The comparison of the results obtained using the traditional one-way coupling approach and the new two-way coupling approach is also done to assess the necessity to use the proposed coupling technique on low adhesion roads, and the combined effect of crosswind and road adhesion on vehicle stability is analyzed. Findings: The results suggest that the lower the road adhesion is, the larger deviation a vehicle generates, the more necessary to conduct the two-way coupling simulation. The combined effect of the crosswind and road adhesion can decrease a vehicle's lateral motion on a high adhesion road after the disappearing of the crosswind. But on a low adhesion road, the vehicle tends to be unstable for its large head wind angle. The vehicle stability in crosswind on a low adhesion road needs more attention, and the investigation should consider the coupling of aerodynamics and vehicle dynamics and the combined effect of crosswind and road adhesion. Originality/value: Developing a new two-way coupling approach which can capture the complex vehicle structures and the road adhesion with MBD model and the completed fluid filed structure with CFD model. The present study might be the first study considering the coupling of crosswind and low adhesion road. The proposed two-way coupling approach will be useful for researchers who study vehicle crosswind stability.